ANALISIS IMPLEMENTASI GERAKAN LITERASI SEKOLAH DI MI MA’HAD ISLAMY PALEMBANG - Tuzzakiyah, Latifah; Muhamad Afandi; Miftahul Husni (STKIP Subang, 2026)
This study aims to examine the implementation of the School Literacy Movement (GLS) at MI Ma’had Islamy Palembang. A qualitative approach was employed, with data collected through observation, interviews, and documentation. The participants included the principal, teachers, and students. The findings indicate that GLS has been implemented through the stages of habituation, development, and learning. The program contributes to the development of students’ reading habits, although several challenges remain, such as limited reading materials, varying levels of reading interest, and insufficient family support. Supporting factors include the school’s commitment, the active role of teachers, and the availability of literacy facilities. Therefore, the implementation of GLS is considered fairly effective, yet it requires further improvement to achieve more optimal outcomes.